Does anatomic subsite influence oral cavity cancer mortality? A SEER database analysis. (8th November 2018) - Farhood, Zachary; Simpson, Matthew; Ward, Gregory M.; Walker, Ronald J.; Osazuwa‐Peters, Nosayaba
Abstract : Objective: To determine if there are differences in mortality from oral cavity squamous cell carcinoma (OCSCC) based on oral cavity (OC) subsites. Methods: Using the Surveillance, Epidemiology, and End Results Program (SEER) 9 database, patients with sequence number 0 or 1 squamous cell OCSCC were analyzed by OC subsite for 5‐year cause‐specific mortality (CSM) from OCSCC. Proportional hazards regression determined the association between 5‐year CSM and OC subsites while controlling for treatment modality, stage, and demographic characteristics using hazard ratios. Significance was set at alpha = 0.05. Results: 20, 647 OC patients were included in the regression analysis. The most commonly diagnosed sites were floor of mouth (34.4%) and oral tongue (34.3%). Floor of mouth, upper gum, and retromolar trigone were associated with lower CSM compared to oral tongue. Not receiving surgery and receiving radiation were associated with increased CSM, and CSM increased with cancer staging when distant or regional disease was compared to localized disease. Also, patients diagnosed at 60 years or older and black patients had increased CSM. Conclusion: Among OCSCC patients, those with oral tongue cancer are more likely to experience CSM than patients with floor of mouth, upper gum, and retromolar trigone cancer. It is important to understand these mortality related differences in the management of OCSCC patients. Understanding subsite‐specific mortality may benefit prognosis counseling of OCSCC patients and elicit subsite‐directed research as a means to improve outcomes. Level of Evidence: NA Laryngoscope, 129:1400–1406, 2019